2017
DOI: 10.3892/mmr.2017.8080
|View full text |Cite
|
Sign up to set email alerts
|

The long noncoding RNA cancer susceptibility candidate 2 inhibits tumor progression in osteosarcoma

Abstract: Long noncoding RNA (lncRNA) has been identified to serve a critical role in the development of various types of cancer. Cancer susceptibility candidate 2 (CASC2) is a cancer‑associated lncRNA. However, whether CASC2 regulates osteosarcoma progression remains unclear. Reverse transcription‑quantitative polymerase chain reaction, western blot, invasion and migration assays were used to evaluate the role of CASC2 in osteosarcoma. The present study reported that CASC2 may inhibit osteosarcoma development. Osteosar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…CASC2 overexpression also inhibited the migration and invasion of BC cells. These findings demonstrated that CASC2 acted as a tumor suppressor in BC tissues and cells, which was in accordance with the function of CASC2 identified in other cancer tissues (30).…”
Section: Discussionsupporting
confidence: 88%
“…CASC2 overexpression also inhibited the migration and invasion of BC cells. These findings demonstrated that CASC2 acted as a tumor suppressor in BC tissues and cells, which was in accordance with the function of CASC2 identified in other cancer tissues (30).…”
Section: Discussionsupporting
confidence: 88%
“…Long noncoding RNAs (lncRNAs), with 200 nucleotides in length, have been considered as transcriptional or posttranscriptional regulators of gene expression. 8 Due to the critical regulation on cell proliferation, migration and invasion, 9 lncRNAs are recently acquired great attention in cancer research. lncRNA hepatocyte nuclear factor 1 homeobox A (HNF1A)-antisense RNA 1 (AS1) is a newly reported lncRNA located on chromosome 13q33.2.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the association between CASC2 and related clinic features is not clear even some is opposite, and the quality of present studies is not good enough. For instance, some studies lack multivariate analysis of clinic pathologic factors for overall survival 21 , 25 , 27 , besides, some studies only provided a Kaplan-Meier curve, but didn't have a specific value of HR 20 , 21 .In addition, the sample of some study is too small 23 .Thus, we generalized and analyzed the clinicopathologic significance and prognostic value of CASC2 in cancer patients. The present comprehensive meta-analysis pooled 11 independent studies with 765 cancer patients and the results indicated that enforced CASC2 pression was a protective factor for OS in cancer patients (HR=0.43, 95% CI: 0.33-0.55, P =0.000).…”
Section: Discussionmentioning
confidence: 99%